Search for bottom-squark pair production in pp collision events at √s=13 TeV with hadronically decaying τ-leptons, b-jets, and missing transverse momentum using the ATLAS detector - Aad, Georges; Andrei, George Victor; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Physical review, 2021)
A search for pair production of bottom squarks in events with hadronically decaying τ-leptons, b-tagged jets, and large missing transverse momentum is presented. The analyzed dataset is based on proton-proton collisions at √s=13 TeV delivered by the Large Hadron Collider and recorded by the ATLAS detector from 2015 to 2018, and corresponds to an integrated luminosity of 139 fb−1. The observed data are compatible with the expected Standard Model background. Results are interpreted in a simplified model where each bottom squark is assumed to decay into the second-lightest neutralino ˜χ02 and a bottom quark, with ˜χ02 decaying into a Higgs boson and the lightest neutralino ˜χ01. The search focuses on final states where at least one Higgs boson decays into a pair of hadronically decaying τ-leptons. This allows the acceptance and thus the sensitivity to be significantly improved relative to the previous results at low masses of the ˜χ02, where bottom-squark masses up to 850 GeV are excluded at the 95% confidence level, assuming a mass difference of 130 GeV between ˜χ02 and ˜χ01. Model-independent upper limits are also set on the cross section of processes beyond the Standard Model.
* ATLAS Collaboration: G. Aad, V. Andrei, F. Bartels, M. Czurylo, S. Dittmeier, M. Dunford, S. Franchino, M. Klassen, A. Krishnan, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, A. Schoening, H.-C. Schultz-Coulon, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, X. Yue [und 2915 weitere Personen]
Gesehen am 11.11.2021